2023
DOI: 10.1002/cam4.5615
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine combined with RDHAP regimen in relapsed/refractory diffuse large B cell lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin lymphoma (NHL), accounting for approximately 30%-40% of cases. The current standard treatment is the R-CHOP regimen, although 30%-40% of patients relapse or develop refractory diseases. 1 Only 13% of these patients undergo high-dose chemotherapy followed by autologous stem cell transplantation (HDT-ASCT). 2 Patients with relapsed/refractory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Some drugs have been confirmed to be effective in the treatment of DLBCL. Kong et al's clinical research confirmed the combined benefit of irditinib with the RDHAP regimen in the treatment of relapsed/refractory DLBCL [ 45 ]. Derek B Oien et al found that in heterologous transplantation models derived from DLBCL cell lines and patients, acatnib combined with AZD5153 demonstrated synergistic benefits [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some drugs have been confirmed to be effective in the treatment of DLBCL. Kong et al's clinical research confirmed the combined benefit of irditinib with the RDHAP regimen in the treatment of relapsed/refractory DLBCL [ 45 ]. Derek B Oien et al found that in heterologous transplantation models derived from DLBCL cell lines and patients, acatnib combined with AZD5153 demonstrated synergistic benefits [ 46 ].…”
Section: Discussionmentioning
confidence: 99%